Macroscopic and microscopic description of phase transition in cerium isotopes - Alexa, P.; Abolghasem, M.; Thiamova, G.; Bonatsos, D.; Rodriguez, T. R.; Reinhard, Paul-Gerhard (Physical Review C - Nuclear Physics, 2022)
The spherical-to-deformed phase transition in cerium isotopes recently suggested to occur between 146Ce and 148Ce has been examined in the framework of the macroscopic algebraic collective model and two microscopic approaches, namely Skyrme-Hartree-Fock + Bardeen-Cooper-Schrieffer (BCS) calculations and the symmetry conserving configuration mixing method with Gogny energy density functionals applied also to the neighboring nuclei along the cerium isotopic chain. Possible spectral signatures of the phase transition are discussed in more details. The microscopic calculations predict octupole softness manifested by rather flat potential energy curves as a function of the octupole deformation parameter beta 3 for 146Ce and 148Ce and shape coexistence characterized by axially symmetric 0+ states, triaxial 2+ bands, and octupole deformation for the lowest 1- states.
CRIS-Team WoS Importer:2022-12-02